Effect of fermentation time on texture properties of coilia spp. and nemipterus spp. fermented using roasted and steam rice - Norasmah Mantali (Institut Akuakultur Tropika, 2011)
Fish is important as a source of protein to human. Therefore, full utilization of fish would give best result of storing the fish during no season of fish. To prolong and maintain the quality, fermented is one of the methods to keep the shelf life lasting and good quality. Fermented fish was produced from two types of fish which is Coilia spp. and Nemipterus spp. The fish was fermented with roasted rice and steamed rice for 30 days.